Investigating the Efficiency and Optimization of Germanium-based Perovskite Solar Cell using SCAPS 1D (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
Germanium-based perovskite solar cells (PSCs) are a substitute for conventional lead-based perovskite solar cells without sacrificing the environment. In this work, simulation has been carried out with the Cesium germanium bromide, CsGeBr3 perovskite solar Cell on SCAPS-1D and the impact of several factors such as the thickness of the absorber layer, operating temperature and defect density is analyzed. The device has achieved maximum power conversion efficiency of 11.35 % with an absorber layer thickness of 600 nm at 305 K. The photovoltaic parameters show that the solar devices are stable at 305 K. This indicates that CsGeBr3 PSC is a promising device for future photovoltaic applications and for designing highly efficient lead-free PSC.